Lower GCS is Related to Poor Outcome among Acute Stroke Patients with COVID-19 in A Tertiary Referral Hospital in Indonesia - Mieke Actress Hanna Nelly Kembuan; Arthur Hendrik Philips Mawuntu; Yohanna Yohanna; Feliana Feliana; Melke Joanne Tumboimbela (The Indonesian Biomedical Journal, 2021)
BACKGROUND: The Coronavirus disease 2019 (COVID-19) pandemic has forced the health workforce to take mitigative measures such as physical distancing, screening, personal protective equipment donning, and confinement on patient care. We aimed to study the outcome of acute stroke patients with suspected, probable, or confirmed COVID-19 in a tertiary referral hospital in Indonesia during the first year of COVID-19 pandemic.METHODS: This was a retrospective study examining all medical records of adult patients suffering from acute stroke with suspected or confirmed COVID-19 who were admitted to R.D. Kandou Hospital, Manado, Indonesia, between March 2020 to March 2021. Clinical and laboratory parameters were compared between subjects with poor and good outcomes based on Glasgow Outcome Scale (GOS), divided into poor outcome (GOS 1-3) and good outcome (GOS 4-5).RESULTS: Fourty-six eligible subjects were enrolled in the study. Based on the GOS, 36 subjects (78.3%) were admitted to the hospital with poor prognosis. On admission, the median Glasgow Coma Scale (GCS) was 11, breathlessness was found in 54.3% of subjects, fever was found in only 15 subjects (32.6%), and the lowest oxygen saturation on admission 95%. We found that GCS significantly related to outcome after controlled for other factors using the logistic regression method (p=0.03; 95% CI=1.08-4.78).CONCLUSION: Lower GCS can be used to predict poor outcome in acute stroke patients with COVID-19.KEYWORDS: COVID-19, acute stroke, Glasgow Coma Scale, outcome, Indonesia